Role of Y Box Protein-1 in cancer: As potential biomarker and novel therapeutic target - Maurya, Pramod Kumar; Mishra, Alok; Yadav, Birendra Singh; Singh, Swati; Kumar, Prashant; Chaudhary, Amit; Srivastava, Shweta; Murugesan, Suriya Narayan; Mani, Dr. Ashutosh (Journal of Cancer, 2017)
The Y-box binding protein (YB-1) is known to be a multifunctional transcription and translation factor during expression of several proteins. It is a vital oncoprotein that regulates cancer cell progression and proliferation. YB-1 is over-expressed in various human cancers such as breast cancer, colon cancer, lung cancer, gastric cancer oesophageal cancer and glioblastoma. Nuclear expression of YB-1 is found to be associated with multidrug resistance and cancer cell progression. YB-1 is reported to regulate many cellular signalling pathways in different types of cancer proliferation. Knowledge about nuclear localization and nuclear level expression of YB-1 in different cancers has been correlated with prospective prognosis of cancer. This review discusses the prospects of YB-1 as a potential biomarker as well as therapeutic target in lieu of their role during cancer progression and multidrug resistance.